Catalytic decomposition of palm oil to liquid fuels and chemicals - Ekramul Mahmud, H. N. M.; Saidina Amin, Nor Aishah; Songip, Ahmad Rahman (1997)
An attempt was made to convert vapours of palm oil to liquid fuels and other chemicals by passing over various zeolite catalysts in a glass reactor. The catalysts used were in the zeolite family namely ultra-stable Y (USY), rare-earth Y (REY) and Na-Y. The liquid products were analyzed by gas chromatography. The results show that it is possible to alter the yield and compositions of the different hydrocarbon products by changing the reactor temperature, the type and amount of the catalyst. USY (6.0g) at the 425 degree C, offered a liquid product (92.63 wt% of total liquid hydrocarbons) in the gasoline boiling range enriched with high content of aromatic hydrocarbons which turns out to be high-octane gasoline. Similar liquid product compositions were by REY (6.0g) at 425 degree C with a liquid product of 95.49wt% of total liquid hydrocarbons, in the gasoline boiling range in which 56.37 wt% of total liquid hydrocarbons, was contributed by benzene, toluene and xylenes alone, which have high octane ratings. Na-Y catalyst (6.0g) produced ample amount of straight chain hydrocarbons (53.77 wt% of total liquid hydrocarbons) at 425 degree C in the gasoline boiling range.